Profitable podcasting : grow your business, expand your platform, and build a nation of true fans - Woessner, Stephen, 1972- (AMACOM, 2018)
Podcasting offers rich opportunities, especially if you get in early and do it right. Based on the author's experience building a 2 million venture from scratch, Profitable Podcasting lays out the precise formula for creating, launching, marketing and monetizing podcasts in any industry. Packed with priceless production help, software recommendations, web and social strategies, schedules, checklists, and examples.